Degree of invasion of Canada goldenrod (Solidago canadensis L.) plays an important role in the variation of plant taxonomic diversity and community stability in eastern China. Issue 6 (3rd October 2019) - Wang, Shu; Wei, Mei; Wu, Bingde; Jiang, Kun; Du, Daolin; Wang, Congyan
Abstract: Understanding the impacts of invaders on plant taxonomic diversity and community stability is significant for understanding the mechanisms underlying successful invasion. This study explored the impacts of the invasive plant Canada goldenrod ( Solidago canadensis L.; goldenrod hereafter) with different degrees of invasion on plant taxonomic diversity and community stability by conducting a comparative study in eastern China. Degree of invasion was divided into the following categories, low (<35%, LDI), moderate (35–75%, MDI), and high (>75%, HDI), on the basis of the relative abundance of goldenrod in the invaded plant communities. Plant diversity, dominance, richness, and plant community stability noticeably decreased under HDI but plant diversity and dominance dramatically increased under LDI compared with the adjacent uninvaded plant communities. Plant diversity, dominance, richness, and community stability markedly declined as the degree of goldenrod invasion increased in the invaded plant communities. The greater plant diversity and dominance observed under LDI may be primarily driven by the passenger effects rather than a driving force of the presence of goldenrod. The greater competitive superiority of goldenrod over coexisting native plants under HDI might allow for invasion and enhance the risk of stochastic local extinction of several native species. A significantly positive diversity‐stability relationship was observed, which may explain the underlying mechanisms for the decreased plant community stability and drastic decline in plant diversity under HDI. Accordingly, the degree of invasion of goldenrod plays an important role in the variation of plant taxonomic diversity and community stability in eastern China. Abstract : This study intends to explore the impacts of the notorious invader Canada goldenrod ( Solidago canadensis L.; goldenrod hereafter) with different degrees of invasion on plant taxonomic diversity and community stability. The invasion degree of goldenrod plays an important role in the variation of plant taxonomic diversity and community stability in East China. Plant community stability was positively associated with plant community dominance before invasion but with both plant community diversity and dominance after invasion.